Overview of Depression Levels in Elderly People at Tresna Werdha Nirwarna Puri Samarinda Social Home - Nada Octavia Rusman; Muhammad Aminuddin (Jurnal Kesehatan Pasak Bumi Kalimantan, 2020)
Background : Depression is a mental disorder characterized by a mood that experiences stress, loss of pleasure or interest, feelings of guilt or low self-esteem, impaired eating or sleeping, reduced energy and concentration (Narulita, 2009). One tool for measuring depression is using the Geriatric Depression Scale (GDS) scale. Objective : To determine the incidence of depression in the elderly that occurred at the Tresna Werdha Nirwana Social Home Puri Samarinda. Method : The study design used a descriptive research type with a survey approach. Performed in May 2019 with 30 respondents at the Tresna Werdha Nirwana Social Home Puri Samarinda. Results : 23 elderly did not experience depression and 7 elderly experienced mild depression. Conclusion : Older people who are not depressed may be caused by coping and good social support. And the elderly who experience mild depression are caused by poor social support, a history of illness and age.Keywords : Depression, elderly